Circular migration: A sustainable concept for migration policy? - Steffen Angenendt (Stiftung Wissenschaft und Politik (SWP), 2007)
In the EU, a new discussion on temporary labour migration is underway, set in motion by a German-French initiative of Ministers of the Interior Wolfgang Schäuble and Nicholas Sarkozy. Their proposal: that the EU states work more closely both to combat illegal migration and to control legal migration, especially by fostering 'circular migration'. The latter idea in particular has been met with criticism. Yet this critical perspective overlooks the fact that the initiative has injected new momentum into the halting development of a European migration policy. At the same time, key aspects must still be clarified to provide a foundation for a sustainable immigration policy. The debate on the open questions should be pushed further, both within the Council and in the other EU institutions.(SWP Comments / SWP)
Keywords: 320